A Systematic Review and Network Meta-Analysis Comparing the Use of Foley Catheters, Misoprostol, and Dinoprostone for Cervical Ripening in the Induction of Labor. Issue 4 (December 2016) - Chen, W.; Xue, J.; Peprah, M.K.; Wen, S.W.; Walker, M.; Gao, Y.; Tang, Y.
Abstract : ( BJOG . 2016;123:346–354) Induction of labor often begins with cervical ripening as other induction techniques, such as oxytocin, are less effective if the cervix is not in a favorable condition. There are various methods available, both mechanical and pharmacological, that soften, thin, and dilate the cervix. It is still debatable which of these cervical ripening techniques is optimal. The goal of this systematic review and network meta-analysis was to compare methods for cervical ripening as a component of labor induction.